Discursive Online Identities. Self-disclosure in Blogs - Oprea, Delia (Acta Universitatis Danubius. Communicatio, 2022)
The current study aims to discern how identities are built within a sample of popular personal blogs and to depict the varieties of identities that can emerge in a digital medium. The focus is placed on the diversity of topics disclosed by the bloggers. Our analysis will take into consideration five popular Romanian blogs. The analysis shows that the topics disclosed in the blogs elucidate facets of online identity created with intention and deliberately by the author and by interaction with the audience. This study examines the construction of personal identities using the Gee (2011) structure of discourse varieties by focusing on self-disclosure in the digital world as expressed in blogs.